Something Old, Something New, Something Borrowed, Something Taboo: Interaction and Creativity in Humour - Maraev, Vladislav; Breitholtz, Ellen; Howes, Christine; Larsson, Staffan; Cooper, Robin (Frontiers in Psychology, 2021)
In this paper we treat humorous situations as a series of events underpinned by topoi, principles of reasoning recognised within a socio-cultural community. We claim that humorous effect in jokes and other discourse is often created by the juxtaposition of topoi evoked. A prerequisite for this is that there is a switch where the interpreter of the discourse updates their information state with regard to a second topos being evoked. This view of humour is consistent with an incremental analysis of dialogue, and we therefore argue that interaction is central both for humour creation and interpretation. We point out some different ways in which topoi are juxtaposed in humorous dialogues as well as in jokes published in social media or in joke books, and take jokes from the coronavirus pandemic as an example because this makes lots of new topoi available and therefore offers the opportunity of creating novel jokes based on the juxtaposition of the new and existing topoi. We explore how the mechanisms of inference in dialogue can be applied to humour through the four elements from our title: old (existing), new (not previously existing), borrowed (associated with a different situation) and taboo (inappropriate in the context).